1994
DOI: 10.1002/mpo.2950220212
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of sequential combination chemotherapy in advanced and recurrent retinoblastoma

Abstract: Eight patients with advanced/recurrent retinoblastomas were treated with sequential combination chemotherapy incorporating cyclophosphamide, cisplatin, adriamycin, and etoposide. All patients achieved complete clinical response (CR) at the end of the first 75 day cycle. Three patients developed recurrence of which 2 patients had recurrence in the central nervous system and 1 patient had local recurrence. Median time to treatment failure was 30 weeks. Two patients succumbed to chemotherapy related neutropenic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Published data regarding the frequency, base range and duration of neutropenia or neutropenic fever after treatment with these drugs are, however, limited. We could only locate data on frequency, and the frequency of neutropenic fever in our patient cohort (41.3%) was comparable to frequencies observed in reports using other chemotherapy protocols (25–100%) 21 22. None of our patients died from sepsis or other chemotherapy-associated side effects.…”
Section: Discussionsupporting
confidence: 71%
“…Published data regarding the frequency, base range and duration of neutropenia or neutropenic fever after treatment with these drugs are, however, limited. We could only locate data on frequency, and the frequency of neutropenic fever in our patient cohort (41.3%) was comparable to frequencies observed in reports using other chemotherapy protocols (25–100%) 21 22. None of our patients died from sepsis or other chemotherapy-associated side effects.…”
Section: Discussionsupporting
confidence: 71%
“…Nevertheless, the utility of ad-juvant chemotherapy in such cases remains debatable, and its role has yet to be clearly defined. [21][22][23][24][25][26][27][28][29][30][31][32][33][34] Adjuvant orbital external beam radiotherapy following enucleation is recommended in patients with tumor invasion of optic nerve transection, scleral and extrascleral extension, spontaneous or accidental ocular perforation, and intraocular surgery for unrecognized retinoblastoma. 6,35 The role of such therapy, however, is not well established.…”
Section: Discussionmentioning
confidence: 99%
“…33 Uusitalo et al 39 concluded that chemoprohylaxis is necessary for patients with tumor invasion of optic nerve transection and is likely to be beneficial in preventing metastasis in patients with retrolaminar optic nerve invasion. 39 On reviewing the published literature regarding the role of adjuvant therapy in high-risk retinoblas- toma, [21][22][23][24][25][26][27][28][29][30][31][32][33][34] it is evident that the major limitations of such studies have been the particular rarity of the end point (metastasis), 21,25,28,33,39 the lack of comparable stratification for subgroup analysis, 21,23,25,26,28,[31][32][33][34] and more significantly, the absence of a control group ( Table 5). 21,25,26,28,[32][33][34] The absence of strict inclusion criteria, the inclusion of a wide variety of cases with bilateral and heritable retinoblastoma, and patients with multiple prior treatments may have introduced confounding variables, making it difficult to objectively interpret the results of these studies.…”
Section: Commentmentioning
confidence: 99%
“…When retinoblastoma is treated in the early stages by enucleation, the cure rates approach 95%. [2][3][4] Besides the loss of vision, this therapeutic approach may leave the child with a facial deformity that worsens throughout life. 5 More advanced disease may require radiotherapy or chemotherapy in addition to enucleation.…”
mentioning
confidence: 99%